A rare cause of MINOCA : Embolism of a thrombus arising from accessory mitral valve tissue - Chan, En Ze; Kang, Giap Swee; Amelia Goh, Xin Chun (Oxford University Press, 2025)
A 51-year-old lady with underlying hypertension presented with angina. Electrocardiogram showed no ischemic changes, but the highly sensitive Troponin I was 203.3ng/L (reference range≤26.2ng/L). Transthoracic echocardiogram demonstrated a left ventricular ejection fraction of 65% with no regional wall motion abnormality but suspicion of posterior mitral valve (MV) leaflet mass with trivial mitral regurgitation with no evidence of valve stenosis. (Panel A, supplementary material online, video S1). Coronary angiogram demonstrated 20% stenosis at the distal left anterior descending artery.